Genetic Susceptibility to Drug Teratogenicity: A Systematic Literature Review - Gomes, Julia do Amaral; Olstad, Emilie Willoch; Kowalski, Thayne Woycinck; Gervin, Kristina; Vianna, Fernanda Sales Luiz; Schüler-Faccini, Lavínia; Nordeng, Hedvig Marie Egeland (Frontiers in Genetics, 2021)
Since the 1960s, drugs have been known to cause teratogenic effects in humans. Such teratogenicity has been postulated to be influenced by genetics. The aim of this review was to provide an overview of current knowledge of genetic susceptibility to drug teratogenicity in humans and reflect on future directions within the field of genetic teratology. We focused on 12 drugs and drug classes with evidence of teratogenic action, as well as 29 drugs and drug classes with conflicting evidence of fetal safety in humans. An extensive literature search was performed in the PubMed and EMBASE databases using terms related to the drugs of interest, congenital anomalies and fetal development abnormalities, and genetic variation and susceptibility. A total of 29 studies were included in the final data extraction. The eligible studies were published between 1999 and 2020 in 10 different countries, and comprised 28 candidate gene and 1 whole-exome sequencing studies. The sample size ranged from 20 to 9,774 individuals. Several drugs were investigated, including antidepressants (9 studies), thalidomide (7 studies), antiepileptic drugs (5 studies), glucocorticoids (4 studies), acetaminophen (2 studies), and sex hormones (estrogens, 1 study; 17-alpha hydroxyprogesterone caproate, 1 study). The main neonatal phenotypic outcomes included perinatal complications, cardiovascular congenital anomalies, and neurodevelopmental outcomes. The review demonstrated that studies on genetic teratology are generally small, heterogeneous, and exhibit inconsistent results. The most convincing findings were genetic variants in SLC6A4, MTHFR, and NR3C1, which were associated with drug teratogenicity by antidepressants, antiepileptics, and glucocorticoids, respectively. Notably, this review demonstrated the large knowledge gap regarding genetic susceptibility to drug teratogenicity, emphasizing the need for further efforts in the field. Future studies may be improved by increasing the sample size and applying genome-wide approaches to promote the interpretation of results. Such studies could support the clinical implementation of genetic screening to provide safer drug use in pregnant women in need of drugs.